2019
DOI: 10.1002/app.47524
|View full text |Cite
|
Sign up to set email alerts
|

Single step modification of micrometer‐sized polystyrene particles by electromagnetic polyaniline and sorption of chromium(VI) metal ions from water

Abstract: This article describes a single‐step reproducible approach for the surface modification of micrometer‐sized polystyrene (PS) core particles to prepare electromagnetic PS/polyaniline–Fe3O4 (PS/PANi–Fe3O4) composite particles. The electromagnetic PANi–Fe3O4 shell was formed by simultaneous seeded chemical oxidative polymerization of aniline and precipitation of Fe3O4 nanoparticles. The weight ratio of PS to aniline was optimized to produce core–shell structure. PS/PANi–Fe3O4 composite particles were used as adso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 77 publications
1
7
0
Order By: Relevance
“…This is in correlation with the previously reported work, which explain that for physical adsorption, the values of Gibb's free energy should range from −20 to zero kJ•mol −1 , but when these values are more than this limit, the adsorption will be chemical [80]. Similarly Debnath et al demonstrated that if the values of enthalpy change range from 84 to 420 kJ•mol −1 , the adsorption will be chemical while when values of enthalpy change less than 84 kJ•mol −1 it indicates physical adsorption [83]. Besides these properties, activation energy also indicates the chemical and physical nature of adsorption.…”
Section: Thermodynamic Of Adsorptionmentioning
confidence: 99%
“…This is in correlation with the previously reported work, which explain that for physical adsorption, the values of Gibb's free energy should range from −20 to zero kJ•mol −1 , but when these values are more than this limit, the adsorption will be chemical [80]. Similarly Debnath et al demonstrated that if the values of enthalpy change range from 84 to 420 kJ•mol −1 , the adsorption will be chemical while when values of enthalpy change less than 84 kJ•mol −1 it indicates physical adsorption [83]. Besides these properties, activation energy also indicates the chemical and physical nature of adsorption.…”
Section: Thermodynamic Of Adsorptionmentioning
confidence: 99%
“…In many countries, there is a growing need for development of more efficient materials for water treatment and purification technologies (chemical precipitation, flocculation, reverse osmosis, solvent extraction, sorption, membrane processes, exchange of ions, etc. ). For instance, Humelnicu et al showed that every material which contains donor atoms (N, S, O, P, etc.) could interact with heavy metals; therefore, they could be used as sorbents, the heavy metal sorbed amounts (tens to hundreds mg per gram sorbent) being strongly influenced by accessibility of these atoms, which act as ligands for the central heavy metal ion .…”
Section: Introductionmentioning
confidence: 99%
“…High temperature was favorable for the adsorption of Cr­(VI), indicating that the adsorption process was an endothermic process. In addition, 1/ n of the Freundlich model was between 0.1 and 0.5, illustrating that Fe 3 O 4 @UiO-66@PANI possessed a strong binding force with Cr­(VI), which was mainly attributed to the electrostatic attraction of protonated imine groups …”
Section: Resultsmentioning
confidence: 97%
“…In addition, 1/n of the Freundlich model was between 0.1 and 0.5, illustrating that Fe 3 O 4 @UiO-66@PANI possessed a strong binding force with Cr(VI), which was mainly attributed to the electrostatic attraction of protonated imine groups. 43 3.5. Adsorption Thermodynamics.…”
Section: Adsorption Kineticsmentioning
confidence: 99%